Formulasi Masker Gel Peel Off Ekstrak Daun Tanaman Porang (Amorphophallus muelleri Blume) yang Stabil Secara Farmaseutik - Vina Purnamasari M; Hamsinah Hamsinah; Anifatul Mu’awanah (Journal of Pharmaceutical and Health Research, 2023)
Porang leaves (Amorphophallus muelleri Blume) have strong antioxidant activity with an IC50 97.054 µg/mL which often used in the development of cosmetics. Purpose of the research was to obtain a pharmaceutically stable formulation of porang leaf extract gel peel-off mask (Amorphophallus muelleri Blume). The research was laboratory experimental. Porang leaf extract peel-off masks were made in 4 formulas with variations in PVA concentrations of 7.5%, 10%, 12.5% and 15%. The peel-off masks obtained were tested for stability including organoleptic testing, homogeneity, syneresis test, adhesion test, spreadability test, dry time test, viscosity and flow properties. The conclusion from the results obtained that porang leaf extract can be formulated in a gel peel-off mask formula. The gel peel-off mask formula of porang leaf extract (Amorphophallus muelleri Blume) with pharmaceutical stability test is formula 3 with a concentration of 12.5% polyvinyl alcohol and formula 4 with a concentration of 15% polyvinyl alcohol. The gel peel-off mask formula is porang leaf extract that qualifies the pharmaceutical stability test.